2018
DOI: 10.1111/imig.12441
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Rootedness, Normative Beliefs and Emigration Intentions of Slovak University Students

Abstract: The aim of this article is to explore normative beliefs (descriptive, injunctive, personal, subjective), rootedness (desire for change, home/family satisfaction) and their interactions in relation to emigration intentions among university students. Binary logistic regression was used to analyse the data obtained from 375 Slovak university students (75.5% females, mean age 22.9, SD=3.0). The analysis showed that personal normative beliefs and desire for change were significantly positively associated with emigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
(112 reference statements)
2
5
0
4
Order By: Relevance
“…Moreover, because the Cronbach's alpha coefficients for the rootedness subscales are relatively low, the psychometric limitations of this scale must be considered. However, there are several studies in which this scale has been used with similar values (Jorgensen & Stedman, 2001;Orosová et al, 2018). Rioux and Mokounkolo (2010) confirmed good psychometric quality of this scale in their study.…”
Section: Conclusion/discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, because the Cronbach's alpha coefficients for the rootedness subscales are relatively low, the psychometric limitations of this scale must be considered. However, there are several studies in which this scale has been used with similar values (Jorgensen & Stedman, 2001;Orosová et al, 2018). Rioux and Mokounkolo (2010) confirmed good psychometric quality of this scale in their study.…”
Section: Conclusion/discussionsupporting
confidence: 61%
“…However, family rootedness was not significantly related to emigration intentions of students studying teaching unlike other students (Hricová et al, 2017). In another study, Orosová, Benka, Hricová, and Kulanová (2018) also found that the desire for change was significantly positively associated with emigration intentions. The home/family rootedness contributed to the emigration intentions only among females.…”
Section: Introductionmentioning
confidence: 83%
“…The dependent variable is measured using a single question: “Do you intend to migrate in Western Europe after graduation?”, with three possible answers: “Yes”, “No” and “I don't know”. Our measurement is in line to that used by Orosová et al () for Slovakian students' migration intentions. Hence, we formulate and test how some of the reasons behind this potential desire to leave the country of origin could be associated with particular family, socio‐demographic and individual values and beliefs.…”
Section: Methodssupporting
confidence: 87%
“…He et al () found that home region is an influential determinant of migration intentions in the case of college students in Japan and China. Orosová et al () stressed that students with a high level of normative beliefs concerning migration, manifesting high rootedness, are less inclined to migrate. When reconsidering the push and pull theory of migration, Gouda et al () emphasized that the push factors for the Irish medical students are basically non‐economic ones, including the negative perceptions regarding their future careers, poor infrastructure at the workplace and lifestyle difficulties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These factors can be classified in various ways such as based on the presumed directionality of their effects on migration (push and pull determinants), according to the level at which they operate (individual/personal, social/community, organisational, national and international factors), by their different domains (economic, political and legal, social, cultural and environmental drivers). As known from other literature on migration decision making (e.g., Creighton, 2013;De Jong, 2000;Lu, 1998) including a few recent studies on students' migration intentions (Cui, Geertman, & Hooimeijer, 2016;Orosová, Benka, Hricová, & Kulanová, 2018), the integration of these typologies with a more general behavioural theory can help to expand the understanding of how the specific factors operate. This further step has, nevertheless, been uncommon in available literature on international students' postgraduation migration so far.…”
Section: Previous Evidence On International Students' Migration Aftmentioning
confidence: 99%